Malícia e humor: leitura das manchetes de capa do Meia Hora - Somogyi, Karla (2014)
The present thesis has as main objective the study of linguistic-discursive mechanisms involved in establishing the discourse based on veiled sexualization of referents as well as humor in newspapers headlines, to understand more deeply the mechanism of construction of meaning in such texts. To this end, headlines expressing veiled eroticism or obscenity from the popular sensationalist newspaper Meia Hora, published during the Olympic Games of London 2012, were selected as corpus of analysis. The research is founded on the study of Preti (2010) about the discourse based on veiled sexualization and obscenities; on the methodology principles of the French school of Discourse Analysis developed by Maingueneau (2010, 2013), supported by Bakhtin (1992, 1997) and on the studies about human interaction by Grice (1982), Goffman (1967) Brown and Levinson (1987); on Ducrot's (1977, 1987) studies of Linguistic Semantics and on the theory developed by Raskin (1985, 1992) inserted into a new interactional social-cognitive perspective of Text Linguistics, that formulates the semantic-linguistic mechanism of humor. In the present work, we observe that the discourse of veiled sexualization and obscenities explores a semantic-linguistic resource that, at the same time, leads to laughter. This resource is based on the partnership between reader and newspaper, in a way that veiled obscenity and humor are explored in the elaboration of sensationalist headlines to recreate the notified facts, as a strategy to produce empathy and closeness, to please a particular readership who shares the same social values and has linguistic competence to take part in a playful usage of language